Maximizing the Efficiency of Vanillin Production by Biocatalyst Enhancement and Process Optimization - Luziatelli, Francesca; Brunetti, Lorenza; Ficca, Anna Grazia; Ruzzi, Maurizio (Frontiers in Bioengineering and Biotechnology, 2019)
The rising demand of bio-vanillin and the possibility to use microbial biotransformation to produce this compound from agro-industrial by-products is economically attractive. However, there are still several bottlenecks, including substrate and product toxicity, formation of undesired products and genetic stability of the recombinant strains, that impede an efficient use of recombinant Escherichia coli strains to make the whole process cost effective. To overcome these problems, we developed a new E. coli strain, named FR13, carrying the Pseudomonas genes encoding feruloyl-CoA synthetase and feruloyl-CoA hydratase/aldolase integrated into the chromosome and, using resting cells, we demonstrated that the vanillin yield and selectivity were strongly affected by the physiological state of the cells, the temperature used for the growth and the recovery of the biomass and the composition and pH of the bioconversion buffer. The substrate consumption rate and the vanillin yield increased using a sodium/potassium phosphate buffer at pH 9.0 as bioconversion medium. Optimization of the bioprocess variables, using response surface methodology, together with the use of a two-phase (solid-liquid) system for the controlled release of ferulic acid allowed us to increase the vanillin yield up to 28.10±0.05 mM. These findings showed that recombinant plasmid-free E. coli strains are promising candidates for the production of vanillin at industrial scale and that a reduction of the cost of the bioconversion process requires approaches that minimize the toxicity of both ferulic acid and vanillin.